Allogeneic haematopoietic cell transplantation for advanced systemic mastocytosis: best practice recommendations on behalf of the EBMT Practice Harmonisation and Guidelines Committee - McLornan, Donal; Czerw, Tomasz; Damaj, Gandhi; Ethell, Mark; Gurnari, Carmelo; Hernández-Boluda, Juan Carlos; Polverelli, Nicola; Schwaab, Juliana; Sockel, Katja; Raffaella, Greco; Onida, Francesco; Sánchez-Ortega, Isabel; et al. (Leukemia, 2024)
Systemic Mastocytosis (SM) is a multifaceted clinically heterogeneous disease. Advanced SM (AdvSM) comprises three entities: aggressive SM (ASM), mast cell leukaemia (MCL) and SM with an associated hematologic neoplasm (SM-AHN), the latter accounting for 60-70% of all AdvSM cases. Detection of a disease-triggering mutation in the KIT gene (esp. KIT D816V) in >90% of the patients with ASM or SM-AHN has led to a significant improvement in therapeutic options by the implementation of two KIT-targeting kinase inhibitors: midostaurin and avapritinib. Although complete remissions have been reported, neither of these targeted agents is ‘curative’ in all patients and the duration of responses varies. The median overall survival, depending on the WHO subtype and scoring result, is approximately 1 to 4 years. Although the European Competence Network on Mastocytosis (ECNM) and American Initiative in Mast Cell Diseases (AIM) consensus groups recommend allogeneic haematopoietic cell transplantation (allo-HCT) in drug-resistant and other high-risk patients, there is a relative lack of information to guide clinicians on which patients with AdvSM should be considered for transplant, and how KIT inhibitors may fit into the transplant algorithm, including their use pre- and post-transplant to optimise outcomes. Following the generation of an expert panel with a specialist interest in allo-HCT and mastocytosis, these best practice recommendations were generated according to the European Society for Blood and Marrow Transplantation (EBMT) Practice Harmonisation and guidelines and ECNM methodology. We aim to provide a practical, clinically relevant and up-to-date framework to guide allo-HCT in AdvsM in 2024 and beyond.